REKONSTRUKSI LKPD PRAKTIKUM OSMOSIS MENGGUNAKAN DIAGRAM VEE BERBASIS ANCOR - Haqiqi, Baharudin Yusuf; Kusnadi, Kusnadi; Amprasto, Amprasto (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This study aims to analyze and reconstruct the Learner Worksheet (LKPD) of osmosis practicum using the Vee Diagram approach. The research method used is descriptive qualitative with ANCOR (Analyze, Try, and Reconstruct) approach. The purpose of this study is to determine and analyze the LKPD on Omosis practicum based on instruments from Novak and Gowin based on Vee Diagram. The results of the analysis showed that the initial LKPD scored 40.74% and was classified as very poor, especially in the aspects of focus questions, objects, theories and concepts, tools and materials, activity steps, and knowledge statements. Based on these results, LKPD reconstruction was carried out to improve existing deficiencies to make it more relevant to the learning objectives of practicum-based biology. The reconstruction includes rearranging the focus question, adding the theory and principles of osmosis, and adjusting the lab work steps to support contextual learning and strengthening students' science process skills. Kata kunci: diagram vee, LKPD, osmosis, praktikum biologi, rekonstruksi